Biomaterial-enabled delivery of SDF-1α at the ventral side of breast cancer cells reveals a crosstalk between cell receptors to promote the invasive phenotype. (May 2017) - Liu, Xi Qiu; Fourel, Laure; Dalonneau, Fabien; Sadir, Rabia; Leal, Salome; Lortat-Jacob, Hugues; Weidenhaupt, Marianne; Albiges-Rizo, Corinne; Picart, Catherine
Abstract: The SDF-1α chemokine (CXCL12) is a potent bioactive chemoattractant known to be involved in hematopoietic stem cell homing and cancer progression. The associated SDF-1α/CXCR4 receptor signaling is a hallmark of aggressive tumors, which can metastasize to distant sites such as lymph nodes, lung and bone. Here, we engineered a biomimetic tumoral niche made of a thin and soft polyelectrolyte film that can retain SDF-1α to present it, in a spatially-controlled manner, at the ventral side of the breast cancer cells. Matrix-bound SDF-1α but not soluble SDF-1α induced a striking increase in cell spreading and migration in a serum-containing medium, which was associated with the formation of lamellipodia and filopodia in MDA-MB231 cells and specifically mediated by CXCR4. Other Knockdown and inhibition experiments revealed that CD44, the major hyaluronan receptor, acted in concert, via a spatial coincidence, to drive a specific matrix-bound SDFα-induced cell response associated with ERK signaling. In contrast, the β1 integrin adhesion receptor played only a minor role on cell polarity. The CXCR4/CD44 mediated cellular response to matrix-bound SDF-1α involved the Rac1 RhoGTPase and was sustained solely in the presence of matrix-bound SDFα, in contrast with the transient signaling observed in response to soluble SDF-1α. Our results highlight that a biomimetic tumoral niche enables to reveal potent cellular effects and so far hidden molecular mechanisms underlying the breast cancer response to chemokines. These results open new insights for the design of future innovative therapies in metastatic cancers, by inhibiting CXCR4-mediated signaling in the tumoral niche via dual targeting of receptors (CXCR4 and CD44) or of associated signaling molecules (CXCR4 and Rac1).